Penentuan Waktu antar Pemesanan Optimal untuk Model Persediaan Probabilistik Multi-Item dengan All-Units Discount dan Kendala Kapasitas Gudang - Koswara, Handi; Lesmono, Dharma (Performa: Media Ilmiah Teknik Industri, 2018)
A good inventory management becomes crucial for a company since it is related to some inventory costs. In managing inventory, in general we need to determine the optimal order quantity and the optimal time to order. In some cases, when supplier offers discount, a company tends to accept this offer although it needs to consider its storage capacity. In this paper, we develop a multi-item probabilistic inventory model with all-units discount and storage space restriction. We employed the Kuhn-Tucker Conditions to find the optimal order policy. From the numerical experiments, we found that when the storage capacity increases then the optimal time to order and the optimal quantity increase but the total cost decreases.